TAP1 and TAP2 genes in nickel allergy - Silvennoinen-Kassinen, S; Ikäheimo, I; Tiilikainen, A (International archives of allergy and immunology, 1997)
The study was undertaken to see whether TAP1 and TAP2 (transporter associated with antigen processing) genes are involved in susceptibility to nickel allergy. The products of these genes are important in antigen transport and processing, making them candidates for disease susceptibility. Fifty-five nickel-sensitive and 54 non-sensitive subjects were TAP1- and TAP2-typed by amplification refractory mutation system - polymerase chain reaction. The allele and phenotype frequencies of TAP2B were significantly (p = 0.019 and 0.012, respectively) increased in nickel-sensitive subjects versus controls. Relative risk (RR) for TAP2B was 2.7 and etiological factor (EF) = 0.46. The allele frequency of TAP2C was decreased among the nickel-sensitive subjects versus controls (p = 0.016). RR for TAP2C was 0.18. In conclusion, TAP2B increases the risk for nickel allergy, the results suggesting a considerably high EF.